2022
DOI: 10.1021/acs.jmedchem.2c00986
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Orally Bioavailable SOS1 Inhibitors for Suppressing KRAS-Driven Carcinoma

Abstract: The interaction between son of sevenless 1 (SOS1) gene and Kirsten rat sarcoma viral oncogene (KRAS) is crucial for activating signals of proliferation and survival in a range of cancers. We previously discovered compound 40a with a tetracyclic quinazoline pharmacophore as a potent orally bioavailable SOS1 inhibitor. Herein, we disclosed the discovery of compound 13c, which substituted the third ring with the seven-membered ring, as a clinical drug candidate for suppressing KRAS-driven tumors. 13c strongly dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…To continue their efforts, the authors designed and synthesized compound 39 (SOS1 IC 50 = 3.9 nM, DLD-1 p-ERK IC 50 = 21 nM) with an expanded C-ring to demonstrate the comparable inhibitory activities to those of 38 (SOS1 IC 50 = 8.4 nM, DLD-1 p-ERK IC 50 = 13 nM). 96 The PK studies of 39 (T 1/2 = 6.68 h, Cl = 11.3 mL/min/kg) in beagle dogs showed a longer half-life and lower elimination rate than BI-3406 (T 1/2 = 3.07 h, Cl = 20 mL/min/kg), leading to a fascinating bioavailability of 87%. Notably, compound 39 showed a lower risk of sudden cardiac death than BI-3406 in the toxicological investigations.…”
Section: Sos1 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To continue their efforts, the authors designed and synthesized compound 39 (SOS1 IC 50 = 3.9 nM, DLD-1 p-ERK IC 50 = 21 nM) with an expanded C-ring to demonstrate the comparable inhibitory activities to those of 38 (SOS1 IC 50 = 8.4 nM, DLD-1 p-ERK IC 50 = 13 nM). 96 The PK studies of 39 (T 1/2 = 6.68 h, Cl = 11.3 mL/min/kg) in beagle dogs showed a longer half-life and lower elimination rate than BI-3406 (T 1/2 = 3.07 h, Cl = 20 mL/min/kg), leading to a fascinating bioavailability of 87%. Notably, compound 39 showed a lower risk of sudden cardiac death than BI-3406 in the toxicological investigations.…”
Section: Sos1 Inhibitorsmentioning
confidence: 99%
“…The similar binding model between 38 and BI-3406 toward SOS1 suggested that the cyclopropane and the D-ring moiety of 38 mimic the tetrahydrofuran counterpart of BI-3406 . To continue their efforts, the authors designed and synthesized compound 39 (SOS1 IC 50 = 3.9 nM, DLD-1 p -ERK IC 50 = 21 nM) with an expanded C-ring to demonstrate the comparable inhibitory activities to those of 38 (SOS1 IC 50 = 8.4 nM, DLD-1 p -ERK IC 50 = 13 nM) . The PK studies of 39 ( T 1/2 = 6.68 h, Cl = 11.3 mL/min/kg) in beagle dogs showed a longer half-life and lower elimination rate than BI-3406 ( T 1/2 = 3.07 h, Cl = 20 mL/min/kg), leading to a fascinating bioavailability of 87%.…”
Section: Small Molecules Targeting Sos1mentioning
confidence: 99%
“…5 In addition to small molecule SOS1 agonists developed by Fesik and colleagues, [6][7][8][9][10][11] a few of the SOS1 inhibitors have also been discovered including BAY293, BI3406, MRTX0902 and others. [12][13][14][15][16] BAY293 was able to disrupt SOS1-KRAS interaction and demonstrated cellular activity in various cancer cell lines in vitro. 12 BI3406 was the first potent SOS1 inhibitor with single digit nanomolar binding affinity and in vivo activities.…”
Section: Introductionmentioning
confidence: 99%
“…Another compound MRTX0902 ( 5 ) developed by Mirati Therapeutics with a phthalazine core also reached the clinical trial stage recently . Similar works have also been reported by Revolution Medicine and He et al for the SOS1 inhibitor tool RMC-0331 ( 6 ) carrying a pyrrolo[3,4- d ]pyrimidin scaffold and the tetracyclic quinazoline SOS1 inhibitors (e.g., 7 ) with favorable druglike properties, respectively …”
mentioning
confidence: 99%
“…20 Similar works have also been reported by Revolution Medicine and He et al for the SOS1 inhibitor tool RMC-0331 ( 6) carrying a pyrrolo [3,4-d]pyrimidin scaffold 21 and the tetracyclic quinazoline SOS1 inhibitors (e.g., 7) with favorable druglike properties, respectively. 22 Our group's research interests focus on the discovery of small molecule probes targeting the KRAS-MAPK pathway. Using the scaffold hopping strategy, we also designed a class of SOS1 inhibitors on the basis of pyrido [2,3-d]pyrimidin-7-one, which is a privileged scaffold in drug development.…”
mentioning
confidence: 99%